Introducing Comfort, Energy, and Behaviours: A review of comfort, health, and energy use: Understanding daily energy use and wellbeing for the development of a new approach to study comfort - SANCHEZ, Marco Antonio ORTIZ (A+BE | Architecture and the Built Environment, 2019)
There is a need for reducing dwellings’ energy consumption while maintaining a comfortable and healthy indoor environment. This review was performed to provide a steppingstone for identifying new methods for studying everyday home energy use and comfort. First, an overview of comfort is given as seen from different disciplines, depicting the subjective and multidimensional nature of comfort. This is followed by the biological component of comfort, reflected as an emotional, behavioural, and physiological reaction to environmental stimuli. Subsequently, links between comfort, health, and wellbeing are introduced. The second part of the review focuses on energy and buildings, with the connection between energy and behaviours-detailing possible explanations of performance gaps, and the pathways from energy to health. To conclude, human sensation of comfort is more complex than the perception of thermal, acoustical, visual stimuli, or air quality environment. Comfort is a reaction to the environment that is strongly influenced by cognitive and behavioural processes. Habits and controllability have been identified as paramount in the links between comfort and energy consumption. In this holistic view of comfort linked to health, comfort is referred to as ‘wellbeing’. he first steps for new directions of the study of comfort and energy are presented.